Medical Device-Related Pressure Injuries: Knowledge Levels of Nurses and the Affecting Factors - Yayman, Kezban; Dag, Gulten Sucu (Galenos Publ House, 2025)
BACKGROUND/AIMS: This study aimed to determine nurses' knowledge of pressure injuries caused by medical devices and the factors that influence this level of knowledge. MATERIALS AND METHODS: This was a cross-sectional descriptive study. The study sample consisted of 252 nurses. Data were collected using face-to-face and online data collection methods with the medical device-related pressure injuries knowledge questionnaire. RESULTS: The mean total score obtained by nurses on the medical device-related pressure injuries knowledge was below 70%, indicating a generally insufficient level of knowledge. The sub-domain prevention and treatment was rated with the highest percentage of correct answers, 67.87% (10.86 +/- 2.43). The staging subdomain had the lowest percentage of correct responses with 31.87% (0.956 +/- 0.715). It was determined that age (p=0.001), gender (p=0.025), and working shift in the clinic (p=0.006) affected the total score average of the medical device-related pressure injury knowledge level. CONCLUSION: The issue of pressure injuries related to medical devices should be given more attention in nursing education.
Keywords: Medical device; pressure injuries; nursing; knowledge